Central pulmonary arteries in idiopathic pulmonary fibrosis: size really matters. Issue 5 (May 2016) - Price, Laura C.; Devaraj, Anand; Wort, S. John
Idiopathic pulmonary fibrosis (IPF) is the most common of the idiopathic interstitial pneumonias and is often associated with pulmonary hypertension (PH). The presence of PH has major implications for a patient with IPF in terms of exercise capacity and mortality [1, 2]. Early and accurate detection of PH is therefore important for prognostication, timing of referral for transplantation and possible entry into clinical trials. The gold standard investigation for confirming PH in this population, as in any patient, remains right heart catheterisation (RHC). However, performing RHC in patients with IPF is not without risk in what is an older population, often with serious comorbidities. Informed referral for RHC, based on clinical signs and noninvasive tests suggestive of PH, is therefore desirable. Unfortunately, clinical signs of PH are often unreliable in patients with any chronic respiratory disease, let alone IPF, and standard tests such as echocardiography can be surprisingly inaccurate [3, 4]. There remains the need, therefore, to further interrogate noninvasive methods of detection of PH in patients with chronic respiratory disease, including IPF. The concept that the size of the pulmonary artery (PA) derived from a computed tomography (CT) scan might predict the presence of PH and even determine outcome in patients with IPF, as suggested by Shin et al. [5] in this issue of the European Respiratory Journal, is therefore very appealing and potentially widely applicable. Despite the uncertainties of why, when it comes to PH risk in IPF, pulmonary artery size clearly matters http://ow.ly/YlKVy